Jornalismo pós-industrial e convergência no contexto das assessorias de imprensa: caso Sebrae-PB - Almeida, Fernando Ivo de (2016)
This research explores the ambience of a post-industrial journalism and journalistic convergence and its impact on the media ecosystem, changing practices in use of newsrooms, with approach from the Jornal da Paraiba and Correio da Paraíba and press office of the Sebrae Paraíba. With methodological design that includes literature review, interviews and observation form, the research traces the journalism context. The survey results point to a scenario of transformations and changes within the press offices and newsrooms with the rise of player and convergence processes that change the work routines and production of these environments, in the process of a postindustrial journalism.